2022
DOI: 10.1093/biolre/ioac064
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic zinc fluxes regulate meiotic progression in Caenorhabditis elegans

Abstract: Zinc influx and efflux events are essential for meiotic progression in oocytes of several mammalian and amphibian species, but it is less clear whether this evolutionary conservation of zinc signals is also important in late-stage germline development in invertebrates. Using quantitative, single cell elemental mapping methods, we find that Caenorhabditis elegans oocytes undergo significant stage-dependent fluctuations in total zinc content, rising by over sevenfold from Prophase I through the beginning of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Dynamic zinc fluxes are essential for meiotic progression in the oocytes of several animals [ 65 ]. Besides, some zinc-finger proteins have been reported to be required for mitosis or meiosis in oocytes or spermatocytes [ 65 67 ]. We found that the initial fat body cell mitosis is also affected by foi knockdown (data not shown), but the underlying mechanisms need investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic zinc fluxes are essential for meiotic progression in the oocytes of several animals [ 65 ]. Besides, some zinc-finger proteins have been reported to be required for mitosis or meiosis in oocytes or spermatocytes [ 65 67 ]. We found that the initial fat body cell mitosis is also affected by foi knockdown (data not shown), but the underlying mechanisms need investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Organ size is controlled by coordinately regulating cell growth and proliferation. Dynamic zinc fluxes are essential for meiotic progression in the oocytes of several animals [65]. Besides, some zinc-finger proteins have been reported to be required for mitosis or meiosis in oocytes or spermatocytes [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Despite accruing Zn 2+ during oocyte maturation, fertilization witnesses a necessary Zn 2+ release into the external milieu, known as “Zn 2+ sparks” (Converse and Thomas, 2020; Kim et al, 2011; Mendoza et al, 2022; Que et al, 2019, 2015; Seeler et al, 2021). This release of Zn 2+ is a conserved event in fertilization across species and is associated with several biological functions, including those related to fending off polyspermy (Kim et al, 2011; Que et al, 2019; Wozniak et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, after fertilization, Zn 2+ levels need to decrease, as Emi2 is a Zn 2+ -associated molecule, and high Zn 2 levels prevent MII exit (Bernhardt et al, 2012; Shoji et al, 2014; Suzuki et al, 2010b). Following the initiation of Ca 2+ oscillations, approximately 10 to 20% of the Zn 2+ accrued during maturation is ejected during the Zn 2+ sparks, a conserved event in vertebrates and invertebrate species (Converse and Thomas, 2020; Kim et al, 2011; Mendoza et al, 2022; Que et al, 2019; Seeler et al, 2021; Tokuhiro and Dean, 2018; Wozniak et al, 2020; Zhang et al, 2016). The use of Zn 2+ chelators such as N,N,N,N-tetrakis (2-pyridinylmethyl)-1,2-ethylenediamine (TPEN) to create Zn 2+ -deficient conditions buttressed the importance of Zn 2+ during meiotic transitions (Kim et al, 2010; Suzuki et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…As an essential trace element, zinc ions play catalytic, structural, and regulatory roles in biological systems (1), including cell signaling (2)(3)(4) and cell cycle control during meiosis and mitosis (5)(6)(7)(8)(9)(10)(11)(12). Zinc fluxes are also associated with numerous physio-pathological processes (3,5,9,(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%